2022
DOI: 10.5624/isd.20220025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different voxel sizes on the accuracy of CBCT measurements of trabecular bone microstructure: A comparative micro-CT study

Abstract: Purpose The aim of this study was to assess the accuracy of cone-beam computed tomographic (CBCT) images obtained using different voxel sizes in measuring trabecular bone microstructure in comparison to micro-CT. Materials and Methods Twelve human skull bones containing posterior-mandibular alveolar bone regions were analyzed. CBCT images were obtained at voxel sizes of 0.075 mm (high: HI) and 0.2 mm (standard: Std), while micro-CT imaging used voxel sizes of 0.06 mm (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Some researchers compared HU from MSCT with GV from CBCT and concluded that the GV was more reliable for detecting and analyzing hypodense structures [ 18 ]. For bone evaluations, it was reported that high-resolution CBCT could be used for imaging quantitative bone morphometry assessment [ 19 ] and suggested there is a positive correlation between the GVs and the HUs values in quantifying bone tissue [ 20 ]. Similarly, it was reported that CBCT was as accurate and reliable as MSCT in predicting bone density and assessing changes in bone density around dental implants [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers compared HU from MSCT with GV from CBCT and concluded that the GV was more reliable for detecting and analyzing hypodense structures [ 18 ]. For bone evaluations, it was reported that high-resolution CBCT could be used for imaging quantitative bone morphometry assessment [ 19 ] and suggested there is a positive correlation between the GVs and the HUs values in quantifying bone tissue [ 20 ]. Similarly, it was reported that CBCT was as accurate and reliable as MSCT in predicting bone density and assessing changes in bone density around dental implants [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This non-destructive and high-resolution method can depict the trabecular network in various shades of grey colour based on the mineral content. Many studies have routinely applied micro-CT in the structural evaluations of trabecular microstructure [ 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 22 Cone-beam CT has mainly been used for trabecular and cortical bone to evaluate the mandible in dental practice. 23…”
mentioning
confidence: 99%
“…21,22 Cone-beam CT has mainly been used for trabecular and cortical bone to evaluate the mandible in dental practice. 23 Two commercially and routinely available CT techniques recently came on the market, with clear improvements in spatial resolution, approximating the diagnostic performances of the previously mentioned imaging techniques for bone microarchitecture: ultra-high-resolution CT (UHR-CT) and photon-counting detector CT (PCD-CT), both with a detector element size of 0.25 mm. 24,25 These new technologies may revolutionize the diagnostic performance of CT, especially to evaluate microscopic structures with high intrinsic contrast, such as vessels and bones.…”
mentioning
confidence: 99%